2008
DOI: 10.2135/cropsci2008.02.0090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Simple Method to Screen Soybean Genotypes for Salt Tolerance

Abstract: RESEARCH N early 20% of the world's cultivated area is aff ected by salinity (Sairam and Tyagi, 2004). Salinity is caused by rock weathering, wind-transported materials, poor-quality irrigation water, and seawater intrusion onto land. The total saline area of North, Central, and South America is 15.8, 2.0, and 129.0 million ha, respectively (Rengasamy, 2006). Overall health of soybean [Glycine max (L.) Merr.] plants and seed yield are aff ected by saline conditions. The threshold salinity for soybean is 5.0 dS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 20 publications
(22 reference statements)
4
66
0
Order By: Relevance
“…The maintenance of plant such as pest control, pathogens and weeds was carried out intensively. Data observations included salt toxicity scores using the method of Dong Lee et al (2008) and total plant dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…The maintenance of plant such as pest control, pathogens and weeds was carried out intensively. Data observations included salt toxicity scores using the method of Dong Lee et al (2008) and total plant dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…Other QTL analyses performed in wheat for Na + tolerance allowed the identification of Nax1 locus, which maps to the region of the TaHKT1;4 gene that contributes to Na + removal from xylem in the leaf sheath avoiding its over-accumulation in leaf blades (Huang et al, 2006). In soybean, genetic variation for salt tolerance has been described and was observed in wild and cultivated soybean species, suggesting that genetic improvement of salt tolerance is feasible (Lee et al, 2008; Qi et al, 2014). A major QTL for salt tolerance was constantly detected on soybean chromosome 3 (linkage group N) in different populations (Lee et al, 2004; Hamwieh et al, 2011).…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
“…The salt concentration was adjusted by adding salt gradually to raise the concentration by 20 -30 mM over two weeks to reach the final concentration of 100 and 70 mM NaCl for pre-flowering and reproductive stages, respectively. The final NaCl concentration was determined according to previous studies in which cultivar differences in salinity tolerance were most clearly distinguished at 100 or 120 mM NaCl (Lee et al, 2008;Valencia et al, 2008). However, the final concentration of the salinity treatment for the reproductive stage was adjusted to a lower level than that for the pre-flowering stage, because salt-induced damage during the reproductive stage became apparent at a concentration of 70 mM NaCl.…”
Section: Saline Treatmentmentioning
confidence: 99%
“…Saline conditions hamper germination, growth (Abel and Mackenzie, 1964;Wang and Shannon, 1999), and nodule formation (Singleton and Bohlool, 1984) in soybean, resulting in significant reductions in seed yield (Parker et al, 1983;Yang and Blanchar, 1993). Studies comparing genetically diverse cultivars have found significant differences in salt tolerance (Parker et al, 1983;Yang and Blanchar, 1993;Lee et al, 2008;Tuncturk et al, 2008;Ghassemi-Golezani et al, 2009;Hakeem et al, 2012;Karim et al, 2012;Mannan et al, 2012).…”
mentioning
confidence: 99%